Locoregional treatment improves survival in de novo bone-only metastatic breast cancer: Long-term results of the prospective, multi-institutional study - protocol BOMET MF14-01 - Soran, Atilla; Doğan, Lütfi; Işık, Arda; Özbaş, Serdar; Can Trabulus, Didem; Demirci, Umut; Karanlık, Hasan; Soyder, Aykut; Dağ, Ahmet; Bilici, Ahmet; Doğan, Mutlu; Şendur, Mehmet Ali Nahit; et al. (Springer, 2023)
[Abstract Not Available]
Keywords: Protocol BOMET MF14-01; Multi-Institutional Study; Long-Term Results